Cats, Kids, and Video Calls: How Working From Home Affects Self-Presentation - Taber, Lee; Whittaker, Steve (2020)
ABSTRACT Working from home (WFH) in response to COVID has reduced boundaries between home and work roles. It has also reduced in-person interaction, replacing it with digital communication including Video and text. We use personality theory to compare self-presentation on these media versus in-person communication. We use surveys and interviews to examine media self-presentation before and during COVID, as well as between different groups of students and office workers. Pre-COVID students presented themselves as more Extraverted, more Agreeable, less Open, and less Neurotic on Video. On Texting they are less Open and Neurotic. During WFH, students are more Agreeable and less Neurotic on Video while still less Neurotic on Texting. The office worker WFH sample is more Agreeable and less Neurotic on Video. We discuss practical and theoretical implications of results, and future research directions. Keywords personality, self-presentation, Video, Texting, media theory, affordances, COVID, students, office workers ABOUT THE AUTHOR/S Lee Taber University of California, Santa Cruz ltaber@ucsc.edu I'm a graduate student at UCSC, interested in how people communicate using technology and how those communications affect us. I look at how people present themselves differently on Facebook and Snapchat, and why. I've examined self-presentation differences on main Instagram accounts as well as Finstas, or "fake" Instagram accounts. I'm also interested in parasocial relationships with lo-fi hip hop beats and how to make a more readable ToS. More here: http://leetaber.com/ Steve Whittaker University of California, Santa Cruz swhittak@ucsc.edu Technology is transforming our everyday lives, how we think, interact and feel. I work at the intersection of Social and Computer Science. I study how technology is affecting fundamental aspects of our everyday lives, and use insights from Social Science to design new digital tools to support memory and collaboration and to help manage personal information. My main current interest is in designing new technologies to promote well-being. Research Areas: Human-computer interaction, digital well-being, computational social science New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).